Cation distribution of Ni–Cu substituted Li-ferrites. Issue 1 (January 2015) - Ramesh, M.; Rao, G.S.N.; Samatha, K.; Parvatheeswara Rao, B.
Abstract: A series of substituted lithium ferrite samples Li0.5− x Ni x Cu x Fe2.5− x O4, with substituent concentration x =0–0.25 in steps of 0.05, were prepared by conventional double sintering ceramic method. The effect of nickel and copper co-substitutions on structural properties of the samples has been studied using X-ray diffraction, scanning electron microscopy, Fourier transform infrared spectroscopy and vibration sample magnetometer techniques. The lattice parameter has been observed to increase with the increase in concentration ( x ) whereas the saturation magnetization was observed to increase from x ≥0.10 onwards. The observed variations are explained by suggesting transfer of a fraction of Cu ions from octahedral sites to tetrahedral sites at higher substituent concentrations. Theoretical lattice parameters and net magnetic moments per formula were calculated for all the samples by carefully assigning cation distributions so as to obtain a satisfactory agreement with experimental results of the same parameters. The observed infrared spectra of the samples with two distinct peaks for tetrahedral and octahedral metal–oxygen complexes further confirm the formation of spinel structures. Also, the observed variation of tetrahedral site radii which has been found in opposite to that of the tetrahedral absorption band further confirms that the proposed cation distributions are accurate for the investigated Li0.5− x Ni x Cu x Fe2.5− x O4 system.